Geological background and structure of the northwestern coastline of Costa Rica - Solano, Juan-Pablo (2021)
Introduction: The Costa Rican northwestern coastline has a wide geological uniqueness that exhibits rocks from different environments such as abyssal plane, continental slope, continental platform, volcanic eruptions (effusive, explosive, and submarine), coastal, erosional (fluvial and gravitatory), intrusions, and upper mantle rocks. Objective: To present the geologic state of the art of the northwestern coastline of Costa Rica through the bibliographic review of geochemical, petrologic, structural, paleontological and geochronological data. Methods: A bibliographic revision was done to propose a state of the art of northwestern coastline of Costa Rica. Results: The geologic record shows eleven stages from the Jurassic to the Holocene. These stages were regrouped from petrologic, structural, geochronologic, stratigraphic and paleontological interpretations in three depositional stages and four compressive tectonic phases. Conclusions: The first depositional stage is volcanic with oceanic affinity between the Jurassic and Upper Cretaceous. The second has a sedimentary predominance with an age range between the Upper Cretaceous and the Miocene. The last depositional stage is a volcanic (effusive and explosive) from the Pliocene until the present. The tectonic phases are associate with different interactions between tectonic plates. The first phase triggered the Santa Elena Ophiolite obduction during the Early Cretaceous. The second phase occurred in the Early Upper Cretaceous – Campanian and is recognized by its current position and surrounding structures. The third phase lasted from the Upper Eocene until the Miocene and its main result was the folding of the Bahía de Salinas sedimentary rocks. Finally, the Quaternary phase created a tilt axis and the aperture for the deposition of pyroclastic density currents in front of the Guanacaste volcanic ridge.